Bax/Bcl-2 Expression Ratio Analysis of Rat Ovary Vitrified with Date Juice Concentrate as a Natural Extracellular Cryoprotectant - Aisyah Safrina; Nova Anita; Ahmad Aulia Jusuf; Rahimi Syaidah; Huriyah Adani Saoemi (Journal of Human Reproductive Sciences)
Background: The use of extremely low temperatures in vitrification is known to cause cryoinjury so that it can trigger the activation of the intrinsic apoptotic pathway, which can damage the structural integrity of the pre-antral follicle. Based on that, it is necessary to use an appropriate cryoprotectant to protect the preserved cell. Aims: This study aimed to identify the potential use of date juice concentrate (DJC) as a natural extracellular cryoprotectant to suppress the rate of apoptosis after vitrification. Settings and Design: This experimental research uses 24 samples of ovarian rats. Rats were fed and drank an ad libitum. Materials and Methods: Ovaries were isolated in the proestrus phase, then processed into slides for immunohistochemistry (IHC) staining using anti-Bax and anti-Bcl-2 antibodies. IHC results were evaluated for the brown colour using ImageJ IHC Profiler. The results were analysed as an optical density and displayed in the Bax/Bcl-2 ratio. Statistical Analysis Used: All data were statistically analysed with either parametric (analysis of various) or non-parametric (Kruskal–Wallis) tests. Results: The combination of EG 7.5% + DJC 15% (KP2) showed the lowest Bax/Bcl-2 ratio in primordial and primary follicles. Meanwhile, the lowest Bax/Bcl-2 ratio in secondary follicles is found in KP4 (EG 15% + DJC 15%). The DJC is known to contain a dominant amount of glucose. The DJC shows antioxidant activity and contains antioxidant compounds, phenols and flavonoids. Conclusion: The sugar content and antioxidant compounds of DJC can protect against follicle membrane damage, so the rate of intrinsic apoptosis pathway is also suppressed initially with Bax protein suppression in the mitochondrial membrane.